Adaptations of Rajasthan Flora to Climate Change: A Case Study (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Adaptations of Rajasthan Flora to Climate Change: A Case StudyGurdeep singhDr. Rachna MidhaRajasthan, known for its arid and semi-arid conditions, presents a unique ecosystem where plant species have evolved various adaptations to cope with extreme climate fluctuations. This paper explores the adaptive strategies of Rajasthan flora in response to climate change, examining ecological, physiological, and genetic adaptations. By focusing on specific plant species and communities, this study aims to provide insights into how arid zone vegetation is responding to environmental challenges and inform conservation strategies.